Simulation of the Flexural Response of Ultrahigh Performance Fiber-Reinforced Concrete with Lattice Fracture Model - Chunping Gu; Qiannan Wang; Wei Sun (Advances in Civil Engineering)
The flexural response of ultrahigh performance fiber-reinforced concrete (UHPFRC) was simulated based on the lattice fracture model. Fiber was modelled as separated beam that was connected to the matrix with interface beams. The simulated results were compared with the experimental results. Deviations occurred at the late stage of the strain-softening period. But both the strain-hardening behavior and multicracking phenomenon were observed in the simulation. The effects of fiber orientation and fiber content were studied with the lattice fracture model. The flexural strength and toughness of UHPFRC improved as the fibers were aligned distributed or the fiber content increased. The proposed model has the potential to help with the materials design of UHPFRC, and the limitations of the model were also discussed in the paper.